2011
DOI: 10.3354/dao02352
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and hematological reference intervals for Krefft’s turtles Emydura macquarii krefftii from the Burnett River Catchment, Australia

Abstract: Biochemical and hematological reference intervals have not previously been reported for Emydura macquarii krefftii. In 2009, 56 E. m. krefftii were captured by hand from the Burnett Catchment, clinically assessed to determine health status and blood sampled. Reference intervals were calculated from the 35 clinically healthy turtles using techniques established in other chelonid species. Aberrant blood results were identified from the 21 clinically unhealthy turtles. Low numbers of observed cases of creatine ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 17 publications
2
10
0
Order By: Relevance
“…However, even if wild M. georgesi currently number as many as 200, the reduction since the disease outbreak is >90% of the historical population. And even if ~400 initially survived, the speed and severity of M. georgesi mortality in summer–autumn 2015 is comparable to extreme cases of amphibian mortality from chytridiomycosis (Hudson et al, ), vastly exceeds the reported impact of previous disease outbreaks in wild Australian freshwater turtle populations (Ariel et al, ; Brooker & Wombey, ; Flint et al, ; Tucker, Kelly, Limpus, Priest, & Guarino, ), and appears to have no counterpart in turtle disease worldwide.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, even if wild M. georgesi currently number as many as 200, the reduction since the disease outbreak is >90% of the historical population. And even if ~400 initially survived, the speed and severity of M. georgesi mortality in summer–autumn 2015 is comparable to extreme cases of amphibian mortality from chytridiomycosis (Hudson et al, ), vastly exceeds the reported impact of previous disease outbreaks in wild Australian freshwater turtle populations (Ariel et al, ; Brooker & Wombey, ; Flint et al, ; Tucker, Kelly, Limpus, Priest, & Guarino, ), and appears to have no counterpart in turtle disease worldwide.…”
Section: Discussionmentioning
confidence: 94%
“…For example, there may be a bias in capture probability according to body size, or turtles caught on the first occasion may become wary and be more difficult to capture on the second occasion. Some individuals may also be cryptic; for example, some turtles may have hidden in benthic leaf litter, underwater rock crevices, undercut banks, or beds of aquatic (Hudson et al, 2016), vastly exceeds the reported impact of previous disease outbreaks in wild Australian freshwater turtle populations (Ariel et al, 2017;Brooker & Wombey, 1986;Flint et al, 2011;Tucker, Kelly, Limpus, Priest, & Guarino, 2002), and appears to have no counterpart in turtle disease worldwide.…”
Section: Growthmentioning
confidence: 99%
“…Prior to commencing antiviral therapy, blood was collected for the evaluation of packed cell volume (PCV) and plasma uric acid (UA) concentrations. The PCV (28 L/L) was within normal limits for other freshwater turtle species and the UA (0.04 mmol/L) was considered within an acceptable range for the species . Treatment with acyclovir (80 mg/kg PO every 24 h; acyclovir 80 mg/mL, privately compounded) was initiated.…”
Section: Case Reportmentioning
confidence: 99%
“…Because of their longevity and close association with the aquatic environment, freshwater turtles can be considered indicators of aquatic environmental health. In addition to being sentinel species for long‐term pollution exposure, they are also at risk of habitat loss or degradation, invasive species and diseases, among other threats . Another calamity of their long life cycle and low reproductive output is that they are exceptionally slow to recover from population declines, even after the cause has been removed .…”
mentioning
confidence: 99%
“…Previous publications concerning the influence of disease on freshwater turtle populations in Australia are based on mass mortality events or general health problems in a population . It is therefore challenging to interpret the presence of microorganisms in sick turtles as pathogenic or commensal because of lack of baseline data.…”
mentioning
confidence: 99%